Laser Speckles in Anisometropic Amblyopia Treatment - Y. V. Matrosova; O. L. Fabrikantov (Oftalʹmologiâ, 2018)
Purpose. To perform the comparative efficacy assessment of complex treatment for average degree anisometropic amblyopia in children using red, green laser speckles and their combination.Patients and methods. 216 children aged 5–9 years old with anisohypermetropia and anisometropic amblyopia of average degree were followed up. Cycloplegic refraction of sighting eye was from +1.5 to +3.0 D, of the amblyopic one — from +3.5 to +8.5 D. All patients underwent the basic treatment course using magnetostimulation and computer programs. Depending on the applied laser the children were divided into three groups: patients of group I underwent the basic course of pleoptics using laser in the red wavelength range, in patients of group II the basic course was supplemented with laser stimulation in the green wavelength range, group III — along with the basic treatment the alternate stimulation by red and green speckles was used, control group IV — received only basic course without any laser stimulation. The best corrected visual acuity before and after the treatment was estimated.Results. Before treatment there were no any significant differences between groups according to age, refraction and best corrected visual acuity. As a result of treatment we received the reliable increase in visual acuity in all groups. The minimum increase was noted in patients who received the basic course of treatment, 15% increase was noted in patients stimulated with green speckle, in patients who underwent red speckle stimulation visual acuity increased by 27%, the maximum increase in visual acuity was achieved in patients who received the combined stimulation by red and green speckles.Conclusion. The paper has proved the high efficacy of combined application of red and green speckles in pleoptic treatment in comparison with their separate usage and traditional basic course.